IAN McEwan’s Depiction of World as a Dystopian Social Space - Aadil Zeffer; Tahir Zaffar (East Asian Journal of Multidisciplinary Research, 2023)
This paper aims to study Ian McEwan’s presentation of the world as a dystopian social space. McEwan paints an ugly picture of the present times and gives a warning to contemporary society against the inhuman cruelties that rock it every moment. The present world confronts alienation, anxiety, fear and death etc. on a daily basis and the fundamental role is played by fiction in expressing such experiences. The novels of McEwan present a bleak and dystopian picture before the readers as the things are going in a horrible direction. It can be inferred that McEwan is trying to bring home the idea of destruction and other mishappenings which have taken a toll on the world and thereby giving a message to the people to act before it is too late.